Comparative analysis of tax incentive policies for investmentattraction: evidence from Ukraine and the European Union - Savitska, Svitlana; Zabolotnyy, Serhiy (Turystyka i Rozwój Regionalny, 2025)
The article outlines the key aspects of investment activity, emphasizing the role offoreign investment and tax incentives as determining factors in the formation of adequateinvestment support. The instruments of tax stimulation of investment activity are considered,with an emphasis on tax benefits, as the most common mechanism of influence. The conductedanalysis revealed the gaps in the coherence and completeness of the tax-incentive frameworkfor investment activity in Ukraine. It has been noted that the current tax preferences do notgenerate the expected inflow of foreign capital and, simultaneously, contribute to the deepeningof the state budget deficit. The investment attractiveness of Ukraine is assessed based on theanalysis of the dynamics of foreign direct investment receipts and indicators of the investmentclimate. It is concluded that the predicted process of post-war economic recovery, based onexternal financing, necessitates a reevaluation of national policies regulating the investmentstimulus, with a particular focus on new challenges and national development priorities.The study substantiates the rationale for adapting the positive elements of the Polishmodel, based on the functioning of special economic zones, to develop an effective systemfor stimulating investment and promoting the structural transformation of the Ukrainianeconomy, taking into account its institutional and territorial characteristics.